"The emotions were like a roller-coaster": a qualitative analysis of e-diary data on healthcare worker resilience and adaptation during the COVID-19 outbreak in Singapore - Alyssa Yenyi Chan; Celene Ting; Lai Gwen Chan; Zoe Jane-Lara Hildon (BMC, 2022)
Abstract Background Uncertainties related to COVID-19 have strained the mental health of healthcare workers (HCWs) worldwide. Gaining the ability to adapt and thrive under pressure will be key to addressing this. We explore what characterises risk, vulnerability and resilient responses of HCWs during the early stages of the outbreak in Singapore. Methods We undertook qualitative theory-guided thematic analysis of e-diary entries from HCWs who navigated the outbreak from June-August 2020. Data were extracted from a subset of an online survey of n = 3616 participants collected across 9 institutions, including restructured hospitals, hospices and affiliated primary care partners. Results N = 663 or 18% submitted qualitative journal entries included for analyses. All professional cadres, local as well as foreign HCWs participated. Themes are reported according to the Loads-Levers-Lifts model of resilience and highlighted in italics. The model assumes that resilience is a dynamic process. Key factors threatening mental health (loading) risk included a notable rise in anxiety, the effects of being separated from loved ones, and experiencing heightened emotions and emotional overload. Bad situations were made worse, prompting vulnerable outcomes when HCWs experienced stigma in the community and effects of "public paranoia"; or under conditions where HCWs ended up feeling like a prisoner with little control or choice when either confined to staff accommodation or placed on quarantine/Stay Home Notices. Those with strife in their place of residence also described already difficult situations at work being aggravated by home life. Protection (lifts) came from being able to muster a sense of optimism about the future or feeling grateful for the pace of life slowing down and having the space to reprioritise. In contrast, when risk factors were present, balancing these in the direction of resilient outcomes was achieved by choosing to re-direct stress into positive narratives, drawing on inner agency, uptake of therapeutic activities, social support as well as faith and prayer and drawing comfort from religious community among other factors. Conclusion The Loads-Levers-Lifts model is used to guide analysis to inform intervention designs. Levers promoting resilience through targeting therapies, workplace policies and awareness campaigns accounting for identified loads are proposed.